2017
DOI: 10.5604/16652681.1231584
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Portal Vein Thrombosis Prior to Liver Transplantation: A Retrospective Cohort Study

Abstract: Patients with HCC were mainly older men diagnosed at an advanced stage. Treatment was associated with better overall survival, but few patients survived to be treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
4
20
0
2
Order By: Relevance
“…HCV infection, alcohol abuse, and fatty liver disease are the major risk factors associated with the development of the disease. These findings corroborate other studies [3,5,19,20].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…HCV infection, alcohol abuse, and fatty liver disease are the major risk factors associated with the development of the disease. These findings corroborate other studies [3,5,19,20].…”
Section: Discussionsupporting
confidence: 83%
“…The serological marker most often used is AFP and diagnostic imaging has been an important instrument to detect lesions in the subclinical stage [3,20]. In the present study, we found serum AFP levels below 400 ng/mL more often at the time HCC diagnosis was performed.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In line with our results, Ghabril et al reported that patients with PVT on organ procurement and transplant network (OPTN) are more susceptible to early adverse events including higher mortality after liver transplantation . In a retrospective cohort, occlusive PVT was associated with increased early posttransplant mortality …”
Section: Discussionmentioning
confidence: 99%